Methodology for the selection of chemical textile products - Toro, Oscar F. (2017)
The development of new processes in the textile industry entails designing methodologies to select adequate supplies that fit these new processes requirements. This paper presents a methodology used to select a textile binder that fulfill technical specifications of a new process to produce nonwoven fabrics, highlighting mainly its ability to form a protective film on the textile fibers and cohesion them without staining, weakening or breaking them. The proposed methodology involves three major phases: (1) consulting textile experts, (2) laboratory tests, and (3) factor weighting. The results indicate that there are two products that can be used in this new process: Arkofil and Size plus AC.